2009
DOI: 10.1109/tro.2009.2019783
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Aided Neurorehabilitation: A Novel Robot for Ankle Rehabilitation

Abstract: In this paper, we present the design and characterization of a novel ankle robot developed at the Massachusetts Institute of Technology (MIT). This robotic module is being tested with stroke patients at Baltimore Veterans Administration Medical Center. The purpose of the ongoing study is to train stroke survivors to overcome common foot drop and balance problems in order to improve their ambulatory performance. Its design follows the same guidelines of our upper extremity designs, i.e., it is a low friction, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
219
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(238 citation statements)
references
References 53 publications
2
219
0
9
Order By: Relevance
“…The design and preclinical characterization, including measurement and torque generation capabilities, of the impedance-controlled anklebot (Interactive Motion Technologies, Inc; Watertown, Massachusetts) have been described in detail elsewhere prior to this pilot study [19]. Briefly, the anklebot is a three-DOF wearable exoskeleton that allows normal ankle ROM in all three DOF of the foot relative to the shank but actuates only DF/PF and INV/EV, with up to 17 Nm of ankle torque.…”
Section: Apparatus (Anklebot)mentioning
confidence: 99%
See 1 more Smart Citation
“…The design and preclinical characterization, including measurement and torque generation capabilities, of the impedance-controlled anklebot (Interactive Motion Technologies, Inc; Watertown, Massachusetts) have been described in detail elsewhere prior to this pilot study [19]. Briefly, the anklebot is a three-DOF wearable exoskeleton that allows normal ankle ROM in all three DOF of the foot relative to the shank but actuates only DF/PF and INV/EV, with up to 17 Nm of ankle torque.…”
Section: Apparatus (Anklebot)mentioning
confidence: 99%
“…At the Baltimore Department of Veterans Affairs (VA), we have developed a modular impedance-controlled ankle robot (anklebot) to deliver task-specific locomotor training aimed at improving paretic ankle contributions to walking and balance function after stroke [19]. The two degree-of-freedom (DOF) anklebot is capable of actuating the ankle joint in dorsiflexion-plantar flexion (DF/PF) as well as inversion-eversion (INV/EV) ranges of motion (ROMs) and is designed to operate in multiple therapeutic settings.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that a variableimpedance orthosis may have certain clinical benefits for the treatment of drop-foot gait compared to conventional ankle-foot orthoses having zero or constant stiffness joint behaviors. The Anklebot developed by Roy et al [20] has been tested to train stroke survivors to overcome common foot drop and balance problems in order to improve their ambulatory performance. Compared with these powered foot orthoses, the CARR was designed for more comprehensive ankle training in a three-dimensional space.…”
Section: Discussionmentioning
confidence: 99%
“…In one group are wearable exoskeletons or powered ankle orthoses developed to control position and motion of the ankle, compensate for weakness, or correct deformities [17][18][19]. With respect to traditional passive foot orthoses, these actuated devices have additional capabilities to promote appropriate gait dynamics for better rehabilitation The MIT Anklebot developed by Roy et al [20] was controlled to adjust the impedance of the orthotic joint throughout the walking cycle for the treatment of drop foot. Park et al [21] developed an active soft ankle orthotic device for use in treating ankle-foot pathologies associated with neuromuscular disorders, including drop foot.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various approaches to develop active orthotic devices using different actuation technologies, such as series elastic actuators (SEA) [3], brushless DC motors [4], McKibben pneumatic artificial muscles [5], [6], and shape memory alloy (SMA) wire springs [7]. Many of these devices are bulky and built on rigid frame structures that constrain the user's natural degrees of freedom of the joint in a manner similar to that of exoskeletons.…”
Section: Introductionmentioning
confidence: 99%